Fueling the fire–a pan-cancer analysis of MYC-regulated lipid metabolism - Chatterjee, Tilottama; Beffert, Ethan; Liefwalker, Daniel (Frontiers in Cell and Developmental Biology, 2025)
The oncogene MYC and its product c-Myc are responsible for a multitude of changes in cancerous cells that trigger cell growth, proliferation and metastasis. The efforts to understand the multifaceted role of MYC in malignancies have highlighted metabolic reprogramming as a prominent function of this transcription factor, with effects across glycolysis, protein and lipid metabolism, mitochondrial respiration and energy storage. In particular, the role of MYC in lipid metabolism has been the focus of several studies in the past two decades, elucidating how the balance of lipid production and breakdown aids in tumor proliferation. Here, we provide a comprehensive summary of how modulation of MYC alters fatty acid synthesis and degradation, the metabolism of compound lipids, and the consequences for other metabolic pathways. The observed effects are highly cell type-specific, highlighting the MYC network’s ability to harness the existing cellular signaling pathways and specific tumor microenvironment to promote tumor growth and metastasis.